The n-fold decrease method of terms number of linguistic variables in risk assessment and task analysis - Корченко, Александр Григорьевич; Ахметов, Бахытжан Сражатдинович; Казмирчук, Светлана Владимировна; Гололобов, Андрей Юрьевич; Сейлова, Нургуль Абадуллаевна (Ukrainian Information Security Research Journal, 2015)
Addressing to the problems of analysis and information securityrisks assessment there is a common need to performthe data processing in fuzzy environments. To implementthis process, the system where an assessment is based onlinguistic variables, based on the standard parametric trapezoidalfuzzy numbers with a specified number of terms isused. The formation of standards is a complex procedurethat is implemented with the experts assistance in correspondingsubject area. In the practical use of mentionedsystem, there is a need for a rapid change of terms, for example,to bring them to a single point. There is a lack ofdescribed capabilities to vary in existing systems. To addresssuch challenge and enhance the effectiveness of riskassessment the n-fold decrease method of terms numbersof linguistic variables is proposed. This method allows tooverride the number of terms of linguistic variables withoutexperts assistance.